PERAN GURU PENDIDIKAN AGAMA ISLAM SEBAGAI MOTIVATOR DALAM PENANAMAN NILAI-NILAI RELIGIUS SISWA - Nabila; Joko Subando (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Teachers play a very important role in strengthening character education for their students, where teachers must exemplify what is conveyed and will be imitated by their students. The formation of attitudes, character, and improvement of skills are guided directly by teachers through exemplary habits. The exemplary behavior exemplified by teachers will facilitate the application of character values ​​for students, in this case forming a child's personality must be done continuously because indirectly children will imitate what is done by the teacher through habits. attention and control from both Islamic Religious Education Teachers and parents. SMP N 6 Surakarta has a vision of forming students who excel and have character. Every Islamic Religious Education teacher must be able to be a motivator so that students' religious values ​​improve day by day with the hope that students are able to be sensitive to themselves, their religion and socially both in the school environment and in the community. With the diverse characters of students, this is a demand and challenge for Islamic Religious Education teachers at SMP Negeri 6 Surakarta.